2016
DOI: 10.1111/bjop.12225
|View full text |Cite
|
Sign up to set email alerts
|

The interaction effect of attentional bias and attentional control on dispositional anxiety among adolescents

Abstract: Research has shown that children and adolescents with attentional control deficits tend to have high anxiety and exhibit threat-related selective attentional bias. This study aimed to investigate how positive and negative attentional biases would interact with attentional control on dispositional anxiety. One hundred and twenty participants aged 18 years of age or younger participated in a visual dot-probe task to measure their attentional bias and completed psychological questionnaires to measure their trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 72 publications
0
6
0
1
Order By: Relevance
“…Exclusion criteria were neurological disorders and any comorbid Axis I disorders. Particularly, in view of the fact that anxiety and depressive symptoms are highly comorbid ( Mineka et al, 1998 ; Kessler et al, 2005 ), and that many studies found a correlation between anxiety and abnormality of attention modulation of emotion (e.g., Mueller et al, 2009 ; Lin et al, 2015 ; Ho et al, 2017 ), we only recruited MDD patients without a diagnosis of anxiety disorder in this study. Furthermore, MDD patients with psychotic features, bipolar disorder, or Axis II disorders were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria were neurological disorders and any comorbid Axis I disorders. Particularly, in view of the fact that anxiety and depressive symptoms are highly comorbid ( Mineka et al, 1998 ; Kessler et al, 2005 ), and that many studies found a correlation between anxiety and abnormality of attention modulation of emotion (e.g., Mueller et al, 2009 ; Lin et al, 2015 ; Ho et al, 2017 ), we only recruited MDD patients without a diagnosis of anxiety disorder in this study. Furthermore, MDD patients with psychotic features, bipolar disorder, or Axis II disorders were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The avoidance behavior commonly found in depressive individuals (Ottenbreit & Dobson, ) might interfere with the selective rehearsal of TBR positive‐valence words, which was an important cognitive process in the item method used in the present study (Basden et al., ). A recent study also showed that anxiety interacts with attentional control on positive attentional bias among adolescents (Ho, Yeung, & Mak, ). Given the high comorbidity of anxiety and depression among young people (Anderson & Hope, ), other potential moderators should be investigated further in future studies (Mitte, ).…”
Section: Discussionmentioning
confidence: 94%
“…However, extremely anxious individuals may not have the attentional control to implement this strategy. The lack of attentional control may, in fact, lead to greater attentional maintenance on arousing stimuli as they are not able to disengage (Ho et al, 2017; Taylor et al, 2016). More research needs to be done to better understand the role of attentional control in these attentional biases and whether valence intensity modulates participants’ ability to employ top-down strategies.…”
Section: Discussionmentioning
confidence: 99%